2020
DOI: 10.1007/s40979-020-00064-4
|View full text |Cite
|
Sign up to set email alerts
|

Students’ awareness of the academic integrity policy at a Latvian university

Abstract: An academic integrity policy usually specifies the university’s ethical principles and values, the forms of appropriate academic behaviour, the penalties for academic malpractice and the procedures for handling policy violations. However, the policy does not itself create academic integrity, but needs to be consistently and effectively communicated, implemented, and applied. This paper presents a case study investigating the extent to which students at Riga Technical University (Latvia) are informed about the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…In this study, the findings show that academic ethical awareness is associated with age, gender, and semester. A study's findings revealed the anticipated association between students' understanding of university policies and how important they believe academic integrity to be for their academic careers, as well as how tolerant they are of infractions of it that encourage educational institutes to develop rules and regulations 20 . In contrast, the studies suggested that junior nursing students have more moral sensitivity that provides a direction for the educators to provide education of academic ethics.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the findings show that academic ethical awareness is associated with age, gender, and semester. A study's findings revealed the anticipated association between students' understanding of university policies and how important they believe academic integrity to be for their academic careers, as well as how tolerant they are of infractions of it that encourage educational institutes to develop rules and regulations 20 . In contrast, the studies suggested that junior nursing students have more moral sensitivity that provides a direction for the educators to provide education of academic ethics.…”
Section: Discussionmentioning
confidence: 99%
“…It is a set of guidelines and standards developed by institutions to promote responsible research and prevent FFP and QRP (Anohina-Naumeca et al, 2020;Labib et al, 2022). They usually cover topics such as authorship, data management, research integrity, conflicts of interest, misconduct, reporting misconduct, and procedures to ensure compliance with ethical and legal standards in research.…”
Section: Ri Policiesmentioning
confidence: 99%
“…An individual semi-structured interview with nine open questions was conducted with all research participants according to the same interview schedule after the pilot study with two teachers. The research method was constructed based on analysis of relevant literature (Anohina-Naumeca, Birzniece & Odiņeca 2020;, Ferguson 2010;Hulbert 2018). Inductive thematic analysis (Braun & Clarke 2006) was applied to the interview transcripts, and, to enhance the trustworthiness of exploration, three authors were engaged in the qualitative data analysis.…”
Section: Data Collection and Analysismentioning
confidence: 99%